2018
DOI: 10.1042/bsr20171457
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of plant isochorismate synthases reveals structural mechanisms underlying their distinct biochemical properties

Abstract: Isochorismate synthase (ICS) converts chorismate into isochorismate, a precursor of primary and secondary metabolites including salicylic acid (SA). SA plays important roles in responses to stress conditions in plants. Many studies have suggested that the function of plant ICSs is regulated at the transcriptional level. In Arabidopsis thaliana, the expression of AtICS1 is induced by stress conditions in parallel with SA synthesis, and AtICS1 is required for SA synthesis. In contrast, the expression of NtICS is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…Another study presents strong evidence for the importance of ICS1 in Arabidopsis. When AtICS1 is expressed in N. benthamiana, a much higher enzymatic activity is observed than for any other plant ICS tested, confirming the importance of ICS1 in Arabidopsis SA accumulation (Yokoo et al, 2018). The avrPphB SUSCEPTIBLE3 (PBS3) enzyme has recently been shown to be responsible for the conversion of IC to SA.…”
Section: Ics Pathway In Plantsmentioning
confidence: 75%
See 1 more Smart Citation
“…Another study presents strong evidence for the importance of ICS1 in Arabidopsis. When AtICS1 is expressed in N. benthamiana, a much higher enzymatic activity is observed than for any other plant ICS tested, confirming the importance of ICS1 in Arabidopsis SA accumulation (Yokoo et al, 2018). The avrPphB SUSCEPTIBLE3 (PBS3) enzyme has recently been shown to be responsible for the conversion of IC to SA.…”
Section: Ics Pathway In Plantsmentioning
confidence: 75%
“…However, WRKY transcription factors regulate a multitude of defense-related genes, such as PAL, which could also be responsible for this increase in SA (Liu et al, 2005(Liu et al, , 2018. Furthermore, it was shown that OsICS has a very low level of enzymatic activity compared to the Arabidopsis homolog (Yokoo et al, 2018). In addition, there is no published research associating OsICS with disease resistance in rice.…”
Section: Ics Pathway In Plantsmentioning
confidence: 99%
“…SIN_1026689 is a WAT1-related protein; SIN_1006025 encodes isochorismate synthase, and SIN_1025056 encodes a betaglucosidase isoform. In plants, isochorismate synthase converts chorismate the last product in the shikimate pathway into isochorismate, a precursor of phylloquinone (vitamin K1) and salicylic acid [37]. In addition, the 17 candidate genes also included 2 chalcone synthase genes SIN_1018961 and SIN_1018959.…”
Section: Candidate Genes Controlling Black Pigment Biosynthesis In Sementioning
confidence: 99%
“…The SA, which is generally involved in the Also, we analyzed the specific biosynthesis genes in SA, JA and ET pathway, 24 respectively. In details, the phenylalanine ammonia-lyase, an enzyme of phenylalanine 25 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 ammonium lyase (PAL) pathway in SA synthesis (Yokoo et al, 2018), was increased in 1 expression at the pre-onset of Phoma sp. infection.…”
Section: Differentially Expressed Genes (Degs) In Un-susceptible and mentioning
confidence: 99%
“…infection. The isochorismate synthase 1, which 2 involved in the synthesis of SA (Yokoo et al, 2018), showed lower expression level in 3 three stages of the susceptible cultivar (Table S1). In the JA pathway, 12-4 oxophytodienoate reductase, which catalyses the reduction of 10, 11-double bonds of (Table S1).…”
Section: Differentially Expressed Genes (Degs) In Un-susceptible and mentioning
confidence: 99%